Copyright Legislations and “Public Good”: A Multinational Survey - Khadka, Santosh (Literary Studies, 2015)
In this article, I survey the domestic copyright legislations of four countries: the USA, India, Sri Lanka, and Nepal, and examine the stated or implied provisions of “public good” across these nations. My inquiry specifically concerns whether or not their copyright legislations take into account the “public good” aspect at all. The Berne Convention provides some space exclusively for developing and underdeveloped countries to include the clauses related to “public good” in their copyright legislations, while same privilege is denied to developed countries. I am, therefore, interested in exploring whether or not developing/underdeveloped countries, like India, Sri Lanka, and Nepal, have taken advantage of that provision and, therefore, whether their legislations have more “public good” provisions compared to their developed counterparts.